The Trials And Tribulations Of Aliakmon: Leigh And Sillivan V. Aliakmon Shipping Co. Ltd. - Marasinghe, L; Singh, Jaginder (Journal of Malaysian and Comparative Law, 2019)
Case note on Leigh And Sillivan V. Aliakmon Shipping Co. Ltd. [1985] 2 WLR 259